Gender and Constraints to Entrepreneurship in Africa: New Evidence from Swaziland - Zuzana Brixiova; Thierry Kangoye (Institute for the Study of Labor (IZA), 2015)
This paper contributes to closing a knowledge gap on gender, entrepreneurship and development by linking the entrepreneurial productivity to start-up capital and skills. The empirical analysis of a survey of entrepreneurs in Swaziland confirmed the importance of start-up capital for sales. Women entrepreneurs have smaller start-up capital and are less likely to fund it from the formal sector than their men counterparts, pointing to a possible room for policy interventions. Further, business training is positively associated with sales performance of men entrepreneurs, but has no effect on women. However, this does not call for abolishing training programs for women entrepreneurs. Instead their design and targeting should be revisited.
Keywords: L53; O12; 330; gender and entrepreneurship; start-up capital; skills; training; multivariate analysis